A rolling horizon approach to the high speed train rescheduling problem in case of a partial segment blockage. (November 2016) - Zhan, Shuguang; Kroon, Leo G.; Zhao, Jun; Peng, Qiyuan
Highlights: We model the real-time timetable rescheduling problem due to a partial segment blockage at a macroscopic level. Three important train rescheduling strategies are introduced and modeled in the partially blocked situation. We assume that the duration of the blockage is a priori unknown. These models are tested on the Chinese high speed railway. Good solutions are achieved in a short computation time by a rolling horizon approach. Abstract: This paper reschedules train services on a double-track high speed railway in a disrupted situation, where one track of a segment is temporarily unavailable. We have to decide the sequence of train services passing through the blocked segment, the arrival and departure time of each train service at each station, and the canceled train services. Three practical train rescheduling strategies are explicitly compared and formulated by three MILP models. The uncertain duration of the disruption is handled. A rolling horizon approach is applied to solve our models. The models are tested on a real-world instance of the Beijing-Shanghai high speed railway.